Liberalizing foodgrains markets: Experiences, impacts, and lessons from South Asia: Synopsis - Ganesh-Kumar, Anand; Roy, Devesh; Gulati, Ashok (International Food Policy Research Institute, 2010)
South Asia is home to the largest concentration of poor and undernourished people in the world, so food security—especially in basic staples such as wheat, rice, and corn—continues to be a major concern. With both persistent and re-emerging food price inflation reaching new heights in 2007-08 in global markets, South Asia saw sharp inflation—between 50 and 100 percent—in basic staples in Bangladesh, Pakistan, and Sri Lanka. These drastic price spikes drew comprehensive policy responses from the governments of these countries, addressing both supply and demand for foodgrains. India, the largest economy in the region, reacted by banning exports of common rice, wheat, and corn, as well as suspending these commodities from futures trading, to ensure comfortable supplies in the domestic market at affordable prices. India also launched a National Food Security Mission in 2007 and announced a special agricultural package (Rashtriya Krishi Vikas Yojana) of roughly US$6 billion to rejuvenate its agriculture. Today, South Asian countries want a greater degree of self-sufficiency; reliance on trade to achieve food security is being questioned by critics. Against this backdrop, a recent book published for the International Food Policy Research Institute (IFPRI) by Oxford University Press, Liberalizing Foodgrains Markets: Experiences, Impact, and Lessons from South Asia, studies the nature of reforms in foodgrains markets (both within-border and at-border reforms), their evolution, and their effects on food economy in general and food security in particular. Through country case studies, editors A. Ganesh-Kumar, Devesh Roy, and Ashok Gulati provide analyses and research-based evidence on decades of food policies in South Asia.